Informal Learning Spaces: Mediated Virtues and Development Practices in a Peri-Urban District of Chongqing, Southwest China - Bonato, Michela (ACME, 2025)
Chongqing, the largest urban agglomeration in its namesake municipality, has experienced rapid urban expansion since the early 2000s, driven by economic growth and land monetisation, bolstered by China’s “Open Up the West” policy. This paper focuses on Beibei District, a peripheral space at the urban-rural interface, which embodies new symbolic and material shifts as part of this urban reconfiguration. Specifically, it examines the use of propaganda posters associated with the China Dream campaign during the redevelopment of selected land plots in Beibei, analysing their content and spatial distribution through a relational socio-semiotic lens. By unpacking the (trans)national and local narratives embedded in these posters, the study reveals how ecological modern neighbourhoods and idealised citizens are co-constructed through public-private spatial encounters. The research critiques the territoriality of power and spatial inequalities, especially in China’s southwestern peripheries, highlighting the entanglement between state-driven urban identity-making and upscale real estate development as a local governmentality tool. It argues that informal learning, facilitated through visual storytelling in public spaces, politicises everyday environments by promoting representations of Chinese virtues. This work contributes to the study of peri-urban micro-spatialities in the Global East, employing a decolonial approach that centres local languages and ontologies for critical reflection on urban knowledge production.